2017
DOI: 10.1007/s11356-017-0933-y
|View full text |Cite
|
Sign up to set email alerts
|

Municipal solid waste compost as a novel sorbent for antimony(V): adsorption and release trials at acidic pH

Abstract: The ability of two municipal solid waste composts (MSW-Cs) to sorb antimony(V) in acidic conditions (pH 4.5) was investigated. Sorption isotherms and kinetics showed that both MSW-Cs could sorb antimony(V), even if in different amounts (~ 0.18 and 0.24 mmol g of Sb(V) by MSW-C1 and MSW-C2, respectively). These differences were ascribed to the chemical composition of composts, as well as to the total acidity of their humic substances. The Sb(V) sorption by both MSW-Cs followed a pseudo-second-order kinetic mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…The MSWC was derived from municipal and green waste composting and was provided by the Facility Plant Secit S.p.A. Consorzio Zir (Chilivani-Ozieri, Italy). The main chemical characteristics of the MSWC are reported in Table S1 and carefully described by Diquattro et al ( 2018 ). Briefly, the compost had a subalkaline pH (i.e., 7.93), a total organic carbon content (27.3% d.m.)…”
Section: Methodsmentioning
confidence: 99%
“…The MSWC was derived from municipal and green waste composting and was provided by the Facility Plant Secit S.p.A. Consorzio Zir (Chilivani-Ozieri, Italy). The main chemical characteristics of the MSWC are reported in Table S1 and carefully described by Diquattro et al ( 2018 ). Briefly, the compost had a subalkaline pH (i.e., 7.93), a total organic carbon content (27.3% d.m.)…”
Section: Methodsmentioning
confidence: 99%
“…51 In particular, Castaldi and co-workers showed that antimony can be removed by chelation with citric and oxalic acids before addition of ethylenediaminetetraacetic acid (EDTA). 52 An analysis of the fitting with the Freundlich isotherm suggests that activated carbon has an adsorption capacity of 214 mg/g compared to around 341 mg/g for [bmim][OTf]. For [bmim][HSO4], values over 500 mg/g can be achieved, further indicating the high adsorption capacity of this solid material due to its high degree of functionality.…”
Section: Extraction Of Metals From Water Using Huminsmentioning
confidence: 97%
“…This is due to a high surface charge density of humic substances and to their functional groups such as carboxyl, phenolic, hydroxyl, carbonyl, and sulfhydryl which are particularly active in the formation of metal-organic complexes. However, the role of MSWC in the mobility of certain anionic contaminants such as Sb(V) [Sb(OH)6 -] or As(V) [H2AsO4 -, HAsO4 2-] is currently under debate (Udovic and McBride, 2012;Sundman et al, 2015;Manzano et al, 2016;Diquattro et al, 2018) and will be further discussed below.…”
Section: Accepted Papermentioning
confidence: 99%
“…Overall, MSWC, RM, WTR and BCH can be considered as environmental friendly amendments that can contribute to the robustness of soil and plants, enhancing crop productivity in problematic and underutilized areas such those contaminated by PTE. Castaldi et al 2005Castaldi et al , 2011Castaldi et al , 2014Castaldi et al , 2015Garau et al, 2007Garau et al, , 2011Garau et al, , 2014Garau et al, , 2017Manzano et al, 2016Manzano et al, , 2020Silvetti et al, 2017;Diquattro et al, 2018;Abou Jaoude et al, 2019Garau et al, 2019b n.d.: not detected Table 2. Influence of MSWC and WTR, added at 4 and 2% (w/w) rate respectively, on selected chemical characteristics of different PTE-contaminated soils (S1, S2 and S3).…”
Section: Accepted Papermentioning
confidence: 99%